Bola3 Regulates Beige Adipocyte Thermogenesis via Maintaining Mitochondrial Homeostasis and Lipolysis - Bai, Ningning; Ma, Jingyuan; Alimujiang, Miriayi; Xu, Jun; Hu, Fan; Xu, Yuejie; Leng, Qingyang; Chen, Shuqing; Li, Xiaohua; Han, Junfeng; Jia, Weiping; Bao, Yuqian; et al. (Frontiers in Endocrinology, 2021)
Mitochondrial iron-sulfur (Fe-S) cluster is an important cofactor for the maturation of Fe-S proteins, which are ubiquitously involved in energy metabolism; however, factors facilitating this process in beige fat have not been established. Here we identified BolA family member 3 (Bola3), as one of 17 mitochondrial Fe-S cluster assembly genes, was the most significant induced gene in the browning program of white adipose tissue. Using lentiviral-delivered shRNA in vitro, we determined that Bola3 deficiency inhibited thermogenesis activity without affecting lipogenesis in differentiated beige adipocytes. The inhibition effect of Bola3 knockdown might be through impairing mitochondrial homeostasis and lipolysis. This was evidenced by the decreased expression of mitochondria related genes and respiratory chain complexes, attenuated mitochondrial formation, reduced mitochondrial maximal respiration and inhibited isoproterenol-stimulated lipolysis. Furthermore, BOLA3 mRNA levels were higher in human deep neck brown fat than in the paired subcutaneous white fat, and were positively correlated with thermogenesis related genes (UCP1, CIDEA, PRDM16, PPARG, COX7A1 and LIPE) expression in human omental adipose depots. This study demonstrates that Bola3 is associated with adipose tissue oxidative capacity both in mice and human, and it plays an indispensable role in beige adipocyte thermogenesis via maintaining mitochondrial homeostasis and adrenergic signaling-induced lipolysis.